THE ROLE OF SOCIAL INVESTING EFFICACY IN MEDIATING THE EFFECT OF INDIVIDUAL VALUES ON ETHICAL INVESTMENT DECISIONS - Hanifa, Khoiro Uma; Atmini, Sari (Jurnal Akuntansi dan Keuangan Indonesia, 2023)
Along with the development of global issues regarding climate change, inequality, and pandemics, ethical investors now can integrate environmental and social aspects through sustainable- and responsible-based investment decisions which allow them to not only focus on financial goals. This study aims to investigate whether individual values, i.e., religiosity, altruism, and egoism, directly influence sustainable- and responsible-based investment decisions. This study also aims to find empirical evidence that those individual values (religiosity, altruism, and egoism) indirectly influence sustainable- and responsible-based investment decisions through social investing efficacy (SIE). The respondents of this study are 96 short-term Indonesian individual investors. Using structural equation modeling, this study does not succeed in finding evidence that religiosity, altruism, and egoism have direct influences on sustainable- and responsible-based investment decisions. However, this study documents that religiosity, altruism, and egoism indirectly influence sustainable- and responsible-based investment decisions through social investing efficacy.